2015
DOI: 10.1097/yco.0000000000000200
|View full text |Cite
|
Sign up to set email alerts
|

Sexual pain disorders

Abstract: http://links.lww.com/YCO/A31.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Nearly 30 million women in the United States suffer from sexual pain disorders, specifically chronic vaginal pain during heterosexual sexual intercourse [1][2][3]. Approximately one in three women will experience chronic vaginal pain during sexual intercourse (CVPDSI) for three or more months at some point in her life [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nearly 30 million women in the United States suffer from sexual pain disorders, specifically chronic vaginal pain during heterosexual sexual intercourse [1][2][3]. Approximately one in three women will experience chronic vaginal pain during sexual intercourse (CVPDSI) for three or more months at some point in her life [1].…”
Section: Introductionmentioning
confidence: 99%
“…Controlled studies have shown that women suffering from the condition report more sexual distress, poorer sexual function, lower sexual satisfaction, and feelings of inadequacy as a sexual partner [5]. Couples experiencing vaginal pain during sexual intercourse report increased intimacy avoidance and greater fear of sustaining their relationship [3,6].…”
Section: Introductionmentioning
confidence: 99%
“…Apesar dos tratamentos disponíveis e orientações de cuidados com a vulva promoverem melhora do quadro álgico, quase sempre são paliativos e não obtem cura ou remissão completa da VVD (72)(73)(74) . Devido à efetividade que os ATCs apresentam em reduzir dores crônicas atuando sobre a atenuação da hipersensibilidade das terminações nervosas, essa classe de medicação tem sido considerada a terapia farmacológica de primeira linha no manejo da dor crônica, de caráter neuropático (75) .…”
Section: Tratamentos Disponíveis Para O Manejo Da Vulvodíniaunclassified